Sistem Kontrol Otomatis Suhu dan Kelembapan Pada Budidaya Jamur Tiram Berbasis IOT - Sujono, Sujono; Arifin, Zaenal (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
Oyster mushroom is a type of food plant that is favored by many people, therefore many people cultivate oyster mushrooms to make a living because they see the large demand for oyster mushrooms, this problem is not matched by sophisticated tools in this cutting edge period. Farmers still use manual tools for mushroom treatment, by making a temperature and humidity monitoring system on mushroom kumbung, farmers can optimize crop yields, the monitoring system built is by installing a DHT 11 sensor around the mushroom kumbung, the sensor can be set by NodMCU and can measure the temperature and humidity in the oyster mushroom kumbung, the temperature and humidity settings are regulated by the NodeMCU which can later be displayed via the Smartphone, the conclusion of this monitoring system is increase the productivity of mushrooms produced by farmers.